A novel colorimetric chemosensor for selective and highly sensitive determination of thiourea: An approach toward a molecular keypad lock. Issue 7 (12th March 2021) - Tavallali, Hossein; Rahimi, Eisa; Deilamy‐Rad, Gohar; Karimi, Mohammad Ali; Tavallali, Maryam
Abstract: A novel simple reversible colorimetric chemosensor has been designed and developed using 4‐(2‐pridylazo) resorcinol (PAR). The colorimetric receptor PAR has been successfully applied for the determination of Hg 2+ ions, and then the PAR‐Hg 2+ complex has been used for thiourea (TU) measurements in aqueous‐buffer medium. This chemosensor exhibited an obvious color change from yellow to bright red in the presence of Hg 2+ in aqueous solution. In addition, the resulting PAR‐Hg 2+ complex sensed TU through naked‐eye, showing recovery from PAR‐Hg 2+ to PAR, in aqueous solution. The detection limits reached up to 3.01 nmol/L for Hg 2+ and 8.5 nmol/L for TU. The operational simplicity and cost‐effectiveness of colorimetric measurements using PAR and Hg 2+ were achieved. Based on this, the designed method was well used to determine the analytes in industrial and environmental samples. The molecular switching between two chemical inputs (Hg 2+, TU) consequences in the IMPLICATION molecular logic gate, which has been integrated sequentially to procedure a sequential information processing device. Abstract : A novel simple reversible colorimetric chemosensor has been designed and developed using 4‐(2‐pridylazo)resorcinol (PAR). The colorimetric receptor PAR has been successfully applied for the determination of Hg 2+ ions, and then PAR‐Hg 2+ complex has been used for thiourea (TU) measurements in aqueous‐buffer medium. The molecular switching between two chemical inputs (Hg 2+, TU) consequences in the IMPLICATION molecular logic gate which has been integrated sequentially to procedure a sequential information processing device.